Oscillating-grid turbulence and its applications : a review/turbulence de grille oscillante et ses applications : une revue - Yan, Jing (2012)
Oscillating-grid turbulence (OGT) is characterized by its zero-mean flow, being two-dimensionally homogeneous in a certain region away from the grid plane. This homogeneous turbulence region that can be readily controlled is suitable for investigating hydraulic problems encountered in environmental engineering. This paper reviews a number of achievements obtained recently in the study of OGT and its applications. Several aspects are discussed including (1) characteristics of the turbulent structure; (2) mass transfer at the interface of air-fluid, solid-fluid or fluid-fluid; (3) sediment entrainment and suspension in zero-mean flow; and (4) utilization of OGT for investigating problems related to environmental engineering. Some suggestions for conducting further studies are also made.